A supernumerary marker chromosome originating from two different regions of chromosome 18. Issue 2 (1st February 2000) - Röthlisberger, Benno; Chrzanowska, Krystyna; Balmer, Damina; Riegel, Mariluce; Schinzel, Albert
Abstract : By random amplification of a microdissected chromosome using the degenerate oligonucleotide primed polymerase chain reaction (DOP-PCR) and forward painting (microFISH), we characterised an extra structurally abnormal chromosome (ESAC) or supernumerary marker chromosome in a mentally retarded girl with a pattern of dysmorphic features. It could be clearly shown that the small marker chromosome originates from two different regions of chromosome 18, 18p11.1→18q11.1 and 18q12.3→18q21.1 respectively. Maternal origin of the de novo ESAC and biparental origin of the normal homologues of chromosome 18 were shown by PCR of several highly polymorphic microsatellites. In this case, application of microFISH was a prerequisite for rapid and precise characterisation of an ESAC. A definite identification of this discontinuous supernumerary marker chromosome would not have been possible using FISH with centromere specific probes or multicolour FISH approaches.